Redactor Is Rabbenu: The Editorial Theology of the Buber-Rosenzweig Bible - Pollock, Benjamin (The Jewish quarterly review, 2026)
In a 1927 letter to Jakob Rosenheim outlining his and Martin Buber’s approach to their translation of the Bible into German, Franz Rosenzweig famously identified “R”—the redactor posited by nineteenth-century Bible scholarship as responsible for the Bible’s final textual unity—as “Rabbenu,” as his and Buber’s authoritative teacher. Drawing on a wealth of unpublished, handwritten materials from Buber’s and Rosenzweig’s collaborative work translating the Bible, this essay poses a series of questions about Rosenzweig’s and Buber’s relationship to this shadowy figure: Who was R, as Buber and Rosenzweig understood him, and what was R’s theology? What might R’s theology have to do with the editorial function typically assigned to R qua redactor, that is, of bringing diverse source documents into their final unified form? What could a commitment to R’s theology entail for Buber and Rosenzweig, and what does this commitment suggest about their own respective theologies? In the course of answering these questions, I make a specific claim regarding the relationship between R’s theology and R’s editorial function, to wit, that, on Rosenzweig’s and Buber’s account, R’s theology of dialectical monotheism goes hand in hand with R’s editorial function and, indeed, that the theological and editorial sides to R’s persona reciprocally inform one another.